Phenotypic analysis and antibiotic susceptibility of methicillin-resistant Staphylococcus aureus in Kiambu County, Kenya - Sani Iliya; Jonathan Mwangi; Ronald Maathai; Mary Muriuki (Journal of Infection in Developing Countries)
Introduction: Methicillin resistant Staphylococcus aureus (MRSA) causes illness to people and can be picked up from both healthcare facilities and the environment leading to high morbidity and mortality. The study was aimed at identifying phenotypic characteristics of Methicillin-Resistant Staphylococcus aureus and determine the antibiotic susceptibility pattern of clinical samples isolated from patients attending or admitted in two health facilities in Kiambu County, Kenya.